Act : the modern actor's handbook - Rotenberg, David (David Charles) (ECW Press, 2021)
"A lively, conversational textbook dedicated to the art of acting from a master teacher. Act: The Modern Actor's Handbook is the result of 30 years of one of North America's most renowned acting teachers teaching some of the world's most talented screen actors. This is a full tour through the concepts at the heart of Rotenberg's techniques: states of being, primaries and secondaries, images that you elaborate up or distill down, modifiers, actions and beats, and more. Although his methods loosely draw on the great acting teachers like Hagen and Meisner back to Stanislavski, he teaches new techniques suited to the best of today's screen actors. This is a major new work in the actor's library and will be pulled off the shelf time and again to find that key into a scene, to prepare for an audition, or to find that right technique to make the art come alive again."--